A Discrimination Discourse on Mongabay.Com: Indonesian Court Jails Environmentalist for Flagging Illegal Farms in Marine Park - Najwa, Nadia; Izzatunnisa , Azka (Cultural Narratives, 2024)
This research reveals the discrimination discourse surrounding the Indonesian court's treatment of environmental activists, specifically focusing on the case of Daniel Frits, who was jailed for exposing illegal shrimp farms in Karimunjawa. The primary objective of this study is to reveal how the media, particularly Mongabay.com, represents the court's actions and the implications of this representation for environmental activism in Indonesia. Using a critical descriptive method and qualitative data, the research analyzes the language and source selection in the article titled "Indonesian Court Jails Environmentalist for Flagging Illegal Farms in Marine Park," published on April 4, 2024. Moreover, Fairclough’s Critical Discourse Analysis uses as approach in this research. The findings indicate that the language used in the article portrays the Indonesian court negatively, suggesting a bias against activists who challenge illegal environmental practices. The analysis reveals that the court's actions are framed as unjust, contributing to a broader narrative that criminalizes environmental advocacy. This representation not only affects public perception of the legal system but also undermines trust in judicial processes related to environmental protection. The implications of this research highlight the significant role of media discourse in shaping public understanding of environmental issues and the legal challenges faced by activists. This study emphasizes the need for greater awareness and support for activists working to protect Indonesia's natural resources.